When Nature Knows Best. - TRICKEY, ERICK (Smithsonian, 2016)
The article discusses research conducted by Dan Nicolau Jr. of McGill University and his son in 2012 which examines whether cytoskeletal proteins can help solve mathematical problems. Nicaolau and his son use a mathematical problem as a graph, which they converted into a microscopic maze that was etched onto a silica chip. The proteins picked up energy from the breakdown of ATP, the energy-releasing molecule that powers cellls.